Maternal cash for better child health?: the impacts of India's IGMSY/PMMVY maternity benefit scheme - Haaren, Paula von; Klonner, Stefan (Discussion paper series, 2020)
The maternity benefit scheme introduced as Indira Gandhi Matritva Sahyog Yojana (IGMSY) in 2011 and renamed Pradhan Mantri Matriva Sahyog Yojana (PMMVY) in 2017, which incentivizes pregnant and lactating women to participate in various infant health-promoting activities, is India's largest conditional cash transfer program thus far. We approach IGMSY's geographically targeted pilot phase as a natural experiment and use data from a large national health survey to estimate its effects by a matched-pair differences-in-differences approach. Consistent with the program's objectives we find positive, albeit small effects on infant immunization as well as long-term health care utilization. In addition, intervals between eligible births increase by 15 percent. Our findings suggest that PMMVY is moderately cost-effective, at least regarding immunization, but that it will make only a small contribution to redressing India's dismal child-health record.
Keywords: Graue Literatur